Climate Risk Analysis on the Food Security in Saguday, Quirino Province - Carandang, Jose Santos R. (Animo Repository, 2014)
Saguday is a 5th-class municipality of Quirino Province. The nine barangays of Saguday namely – La Paz, Cardenas, Salvacion, Santo Tomas, Rizal, Tres Reyes, Dibul, Cardenas and Gamis – are all vulnerable to climate change and calamities, not only because of the scarce resources of the municipality, but also due to the geographical and climatological condition of the area. Rainfall rates are projected to increase due to climate change and there will also be some likely increase in mean maximum tropical cyclone wind speed due to the projected 21st century warming (Knutson et al., 2010). Its location in Quirino Province places Saguday within the biggest watershed area in the region. Both observational data and modelling projections show that with climate change, wet regions will generally (but not universally) become wetter. Crop production in Saguday may also be affected biophysically by meteorological variables including rising temperatures, changing precipitation regimes, and increased atmospheric carbon dioxide levels. As socio-economic factors influence responses to changes in crop productivity with price changes and shifts in comparative advantage, a 5th class municipality with scarce resources can be very vulnerable to the effects of climate change. This present study identifi es the climatological problems and difficulties confronting the municipality.